Comparison of Risk of Serious Cardiovascular Events after Hemorrhagic versus Ischemic Stroke: A Population-Based Study - Akyea, Ralph K.; Georgiopoulos, Georgios; Iyen, Barbara; Kai, Joe; Qureshi, Nadeem; Ntaios, George (Thrombosis and Haemostasis, 2022)
Background Patients with ischemic stroke are considered a very high risk population for subsequent cardiovascular events and guidelines recommend intensive preventive strategies. However, there is no clear recommendation that patients with hemorrhagic stroke should also be regarded as a very high cardiovascular risk population.Objective To compare the risk of subsequent cardiovascular morbidity/mortality between patients with incident hemorrhagic and ischemic stroke.Methods Patients aged ≥18 years with incident hemorrhagic or ischemic stroke between 1998 and 2017 and no prior history of serious vascular event were identified from UK Clinical Practice Research Datalink (CPRD GOLD) linked to Hospital Episode Statistics data.Results The cohort included 32,091 patients with an overall follow-up of 381,237 person-years (median: 11.8 years). After adjusting for potential confounders, patients with incident hemorrhagic stroke had no significantly different risk of subsequent cardiovascular morbidity compared with patients with incident ischemic stroke—coronary heart disease (CHD; hazard ratio [HR]: 0.86, 95% confidence interval [CI]: 0.56–1.32), recurrent stroke (HR: 0.92, 95% CI: 0.83–1.02), peripheral vascular disease (PVD; HR: 1.15, 95% CI:0.56–2.38), or heart failure (HR: 1.03, 95% CI: 0.61–1.74). Patients with incident hemorrhagic stroke had significantly higher risk of subsequent cardiovascular disease (CVD)-related mortality (HR: 2.35, 95% CI: 2.04–2.72) and all-cause mortality (HR: 2.16, 95% CI: 1.94–2.41). Propensity-score matched analysis of 1,039 patients with hemorrhagic stroke and 1,039 with ischemic stroke showed similar risk in subsequent cardiovascular morbidity—CHD (stratified HR [sHR]: 0.92, 95% CI: 0.55–1.54), recurrent stroke (sHR: 0.93, 95% CI: 0.82–1.02), PVD (sHR: 1.04 95% CI: 0.45–2.41), or heart failure (sHR: 0.71, 95% CI: 0.39–1.27).Conclusion The risk of subsequent cardiovascular events is similar between patients with incident hemorrhagic and ischemic stroke. Patients with previous hemorrhagic stroke should be regarded as a population at very high risk for subsequent CVD.
Keywords: hemorrhagic stroke; ischemic stroke; propensity-score matching; electronic health records; cardiovascular outcomes